A sound history : Lawrence Gellert, Black musical protest, and White denial - Garabedian, Steven P. (American popular music (Amherst, Mass.), 2020)
"Lawrence Gellert has long been a mysterious figure in American folk and blues studies, gaining prominence in the left-wing folk revival of the 1930s for his fieldwork in the U.S. South. A 'lean, straggly-haired New Yorker,' as Time magazine called him, Gellert was an independent music collector, without formal training, credentials, or affiliation. At a time of institutionalized suppression, he worked to introduce white audiences to a tradition of black musical protest that had been denied and overlooked by prior white collectors. By the folk and blues revival of the 1960s, however, when his work would again seem apt in the context of the civil rights movement, Gellert and his collection of Negro Songs of Protest were a conspicuous absence. A few leading figures in the revival defamed Gellert as a fraud, dismissing his archive of black vernacular protest as a fabrication-an example of left-wing propaganda and white interference. A Sound History is the story of an individual life, an excavation of African American musical resistance and dominant white historiography, and a cultural history of radical possibility and reversal in the defining middle decades of the U.S. twentieth century."--